15 Clinical outcomes in patients treated with glycoprotein IIB/IIIA inhibitors during primary percutaneous coronary intervention according to arterial access site. (June 2018) - Krishnamurthy, Arvindra; Keeble, Claire; Anderson, Michelle; Somers, Kathryn; Burton-Wood, Natalie; Harland, Charlotte; Baxter, Paul; McLenachan, James; Blaxill, Jonathan; Blackman, Daniel; Malkin, Christopher; Wheatcroft, Stephen; et al.
Abstract : Background: There are little available contemporary real-world data in the era of third-generation P2Y12-receptor inhibitors, examining the association between glycoprotein IIb/IIIa inhibitors (GPI) and outcomes in patients undergoing primary percutaneous coronary intervention (PPCI) for ST-segment elevation myocardial infarction (STEMI), according to arterial access site. Objectives: We sought to investigate this association in a contemporary cohort of real-world patients. Methods: Clinical and follow-up data for all patients undergoing PPCI in Leeds General Infirmary between 01–01–2009 and 31–12–2011, and 01–01–2013 and 31–12–2013 were collected prospectively. Patients included in this analysis had pre-procedural Thrombolysis in Myocardial Infarction (TIMI)−0 flow and post-procedural TIMI-3 flow in their infarct-related artery. Clinical endpoints were 30 day and 12 month mortality, and 30 day HORIZONS-major bleeding. Patients were analysed according to arterial access site with Cox-regression models, to assess the association between GPI use and outcomes in each group (transfemoral PPCI and transradial PPCI), adjusting for confounding variables. Results: A total of 2369 patients were included in this analysis, of whom 821 (34.7%) underwent transfemoral PPCI and 1548 (65.3%) underwent transradial PPCI (Figure 1). GPI was used in 169 (20.6%) patients undergoing transfemoral PPCI, and 179 (11.6%) patients undergoing transradial PPCI. In transfemoral PPCI, GPI use was independently associated with 30 day mortality (HR 2.04 (1.05–3.94); p=0.03) and 30 day bleeding (HR 2.05 (1.07–3.93); p=0.03), particularly arterial access site bleeding (HR 2.71 (1.00–7.37); p=0.05), with no significant difference in 12 month mortality (HR 1.48 (0.82–2.67); p=0.20) (Table 1; Figures 2 (A)-(C)). However, in transradial PPCI, GPI use was not associated with 30 day (HR 1.27 (0.39–4.16); p=0.69) or 12 month (HR 1.21 (0.58–2.51); p=s0.62) mortality, or 30 day bleeding (HR 1.93 (0.73–4.76); p=0.16) (Figures 3 (A)-(C)). Conclusion: In transfemoral PPCI, GPI use was independently associated with worse 30 day mortality and 30 day bleeding, particularly access-site bleeding. This association was not observed in transradial PPCI.